2018
DOI: 10.1186/s12866-018-1216-6
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Lactobacillus casei ghosts by Holin-mediated inactivation and the potential as a safe and effective vehicle for the delivery of DNA vaccines

Abstract: BackgroundBacterial ghosts (BGs) are empty bacterial cell envelopes generated by releasing the cellular contents. In this study, a phage infecting Lactobacillus casei ATCC 393 (L. casei 393) was isolated and designated Lcb. We aimed at using L. casei 393 as an antigen delivery system to express phage-derived holin for development of BGs.ResultsA gene fragment encoding holin of Lcb (hocb) was amplified by polymerase chain reaction (PCR). We used L. casei 393 as an antigen delivery system to construct the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Nevertheless, literature reports on the use of Lactobacillus acidophilus (LA) and other probiotic ghosts as drug carriers are scarce. One study reported the use of Lactobacillus casei ghosts as a potential carrier for DNA vaccines [29]. Among the best known lactic acid bacteria, LA naturally colonizes the human colon with resilient adhesive properties as a result of binding to mucin [30] and recognition of their antigens by colon cells and the adjacent immune system [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, literature reports on the use of Lactobacillus acidophilus (LA) and other probiotic ghosts as drug carriers are scarce. One study reported the use of Lactobacillus casei ghosts as a potential carrier for DNA vaccines [29]. Among the best known lactic acid bacteria, LA naturally colonizes the human colon with resilient adhesive properties as a result of binding to mucin [30] and recognition of their antigens by colon cells and the adjacent immune system [31].…”
Section: Introductionmentioning
confidence: 99%
“…Phages were able to perform the function of phagocytic bacteria, mainly because it could undergo two different life cycles: the holing cycle and the endolysin cycle [21]. In this study, ORF 50 and ORF 51 were defined as regions encoding holin and endolysin .Phage endolysins accumulated in the host cell cytoplasm during phage development [22], until holins suddenly induce formation of holes in the cytoplasmic membrane [23].These holes provided a pathway for endolysin release to the cell wall that was rapidly cleaved, leading to cell burst [24].Therefore, the holin function had the crucial role of defining the time of lysis, which was fundamental for phage fitness. By clearly localized the enzymes of holin and lyase genes, it could provide a feasible idea for exploring the phage lysis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…After phagocytosis, plasmid DNA is released from phagolysosome, and the numerous bacteria-associated danger signals result in profound APC activation [ 226 ]. More recently, ‘bacterial ghosts’ which constitute only the bacterial envelope have been introduced as carriers for DNA vaccines [ 227 ]. Aside oral application, bacteria were shown to confer transfection of APC when applied at other mucosal sites, e.g., when applied intranasally [ 228 ].…”
Section: Route Of Vaccinationmentioning
confidence: 99%